2019
DOI: 10.1158/0008-5472.can-18-1357
|View full text |Cite
|
Sign up to set email alerts
|

ID1 Is Critical for Tumorigenesis and Regulates Chemoresistance in Glioblastoma

Abstract: Glioblastoma is the most common primary brain tumor in adults. While the introduction of temozolomide chemotherapy has increased long-term survivorship, treatment failure and rapid tumor recurrence remains universal. The transcriptional regulatory protein, inhibitor of DNA-binding-1 (ID1), is a key regulator of cell phenotype in cancer. We show that CRISPR-mediated knockout of ID1 in glioblastoma cells, breast adenocarcinoma cells, and melanoma cells dramatically reduced tumor progression in all three cancer s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 58 publications
2
36
0
Order By: Relevance
“…Interestingly, unsupervised hierarchical clustering analysis identified an expression pattern in line with the G007-LK sensitivity; the most sensitive cultures (T0965 and T1008) clustered apart from the least sensitive cultures (T1023 and T2609; Figure S1a). The least sensitive cultures displayed significantly higher expression of genes related to GBM progression and GSC proliferation and stemness, including SPARCL1, HOPX, ID1, ID3, CPE and CXRC4 (Table S1) [36][37][38][39]. However, when analyzing the cultures based on GSC subtypes [40,41], they all displayed a proneural rather than a mesenchymal signature ( Figure S1b).…”
Section: Global Gene Expression Analysis Reveals That Gsc Cultures CLmentioning
confidence: 99%
“…Interestingly, unsupervised hierarchical clustering analysis identified an expression pattern in line with the G007-LK sensitivity; the most sensitive cultures (T0965 and T1008) clustered apart from the least sensitive cultures (T1023 and T2609; Figure S1a). The least sensitive cultures displayed significantly higher expression of genes related to GBM progression and GSC proliferation and stemness, including SPARCL1, HOPX, ID1, ID3, CPE and CXRC4 (Table S1) [36][37][38][39]. However, when analyzing the cultures based on GSC subtypes [40,41], they all displayed a proneural rather than a mesenchymal signature ( Figure S1b).…”
Section: Global Gene Expression Analysis Reveals That Gsc Cultures CLmentioning
confidence: 99%
“…And HCC patients with low expression had a poor survival time, and further biological experiments in vitro and in vivo confirmed that DAMTSL3 and PTEN promoted the proliferation and metastasis of HCC cells [34]. A recent study reported that ID1 acted as a transcriptional regulator and played a critical role for glioblastoma initiation and chemoresistance, and ID1 knockdown promoted the treatment effect of temozolomide, delays tumor recurrence, and prolongs survival [35]. Reportedly, a recent study found that mitochondrial impairment activated the Wallerian pathway and caused the axon degeneration by the depletion of NMNAT2 [36].…”
Section: Discussionmentioning
confidence: 86%
“…Id1 serves as a main mediator that abrogates differentiation signals in glioblastoma stem cells (GSCs) and contributes to GBM initiation and chemoresistance in GBM. Knocking out of Id1 in GBM reduced tumor progression [32]. Study shows that Id1 can simultaneously regulates stemness through WNT/SHH signaling and differentiation through bone morphogenetic protein receptor(BMPR)mediated differentiation signaling in GSCs.…”
Section: Glioblastomamentioning
confidence: 95%
“…Mechanism was found to be via EP4-dependent activation of MAPK signaling and the Egr1 transcription factor [115]. And the inhibition of Id1 enhances the effect of temozolomide, delays tumor recurrence, and prolongs survival [32]. But an opposite conclusion was also acquired by Guo, Q et al who found that GBM patients with high Id1 expression had better survival than patients with low Id1 expression since Id1 expression could increase the radiotherapy efficacy [116].…”
Section: Id1 In Therapeutic Resistancementioning
confidence: 98%